(untitled) (EAAE Annual Conference Proceedings, 2023)
Mental Spaces / Real Spaces - a Digital Archive, is a community research project supported by the government programme Bairros Saudáveis launched during the pandemic. It involved the local community of the Alto dos Barronhos, the largest social housing estate in the municipality of Oeiras, in a set of participatory actions between Architecture and Mental Health with the local community. Questioning what it is to inhabit social housing, the public space was transformed into a space of critical redefinitions.